Improving the Quality of Human Resources through Children Care School Program - Akhmad Taufik (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Work is one of the most critical aspects of human life, so it needs to be carefully planned. However, the reality on the ground shows that unemployment data is increasing from year to year. The problem is exacerbated by the phenomenon of the number of students who feel the wrong direction. Referring to the psychological consultation unit of the Faculty of Psychology UGM, many cases show the number of students who want to move majors because they feel unsuitable or choose the wrong majors for various reasons. These reasons include not understanding the world of career, follow-up friends, or coercion of parents. The impact of selecting a long-term department is a waste of costs, psychological and physical burden. Reality is one of them driven by globalization and technological development. It changes the map and how a person acquires and develops a career, such as a reduced need to work in an office, or should always be a civil servant. Therefore schools should have changed the orientation of vision and mission of education is not "just" just prepare for the exam of the UN, graduated with the highest ranking, and accepted in famous college. Schools must reform the vision and mission of equipping skills that can support the success of its graduates in the new economic waves.